Effect of the addition of enological stabilizers on the wine filterability index: application of simplex-centroid - Gava, Angelo; Ficagna, Evandro; Rossato, Simone; Cisilotto, Bruno; Emer, Cassandro; Borsato, Dionísio (Revista Ciência Agronômica, 2021)
The search for quality improvement in wine has intensified the use of products and additives in the different stages of winemaking, from the receipt of the grapes until the bottling. Among the additives employed at the end of the process, we can cite the arabic gum, mannoproteins and carboxymethylcellulose (CMC). However, the addition of these products most of the times, is performed immediately before the final filtration, which can lead to inefficiency due to membrane clogging and also causing the retention of these stabilizers. The objective of this work was to evaluate the effect of different oenological stabilizers on the wine filterability index (FI) and its turbidity. The products were added to a white wine after tangential filtration (0.22 μm). Experimental design was used for mixtures, simplex-centroid. The maximum limits for each additive were established according to the current brazilian legislation, using the following products and doses: 0.3 g L -1 Arabic gum, 0.15 g L -1 of Mannoprotein and 0.1 g L -1 of CMC. The index was measured using specific software connected to the Vessel Data Filterability Index, developed and owned by AEB Engineering. The addition of mannoprotein compromises the filterability index and increases the turbidity of the wine. The application of CMC and arabic gum does not result in an IF enhancement that makes filtration impossible, the same effect occurs with turbidity. The presence of CMC and/or arabic gum produces an antagonistic effect, reducing the filterability index that the mannoprotein alone would result.